Gaya Bahasa Pada Antologi Cerpen Angsa Berkaki Lima Karya Siswa SMP Negeri 1 Kupang Tengah - Nubatonis, Honis Yuda (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
The problem in this research is to identify the language styles present in 3 short story (Portrait of a Mother, A Mother's Love, and Siblings but Enemies), in the book Anthology of Short Stories Goose with Five Legs by Students of Central Kupang 1 State Junior High School which has the ISBN number 978-602-73153-9-6 monitored by Valentina L. Tanate, S.Pd. The aim of this research is to find out what language styles are found in the three short stories (Portrait of a Mother, A Mother's Love, and Siblings but Enemies) in the book Anthology of Short Stories Goose with Five Legs by Students of Central Kupang 1 State Junior High School. The theory used in this research is stylistics with a qualitative approach. The results of this study are two types of language styles namely the comparative language style and the affirmative language style found in the three short stories. The comparative language styles found in the three short stories include metaphors, litotes, hyperbole and similes. The language styles of affirmation found in the three short stories include antanaclasis, climax, invocation, inversion, pararhyme, anticlimax, personification, anaphora, pleonasm, and repetition.